Functional analysis of intron 3 in the regulation of gene expression of the human lipoprotein lipase gene: Functional analysis of intron 3 in human LPL - Sabri, Noorhan H.; Bastaki, Nasmah K.; Al-Bustan, Suzanne A. (Cellular and Molecular Biology, 2025)
Lipoprotein lipase (LPL) is a key enzyme that hydrolyzes triglycerides (TGs) into free fatty acids. Several genetic variants of LPL are directly or indirectly associated with variations in lipid levels, causing different lipid metabolic disorders. Previous studies on the LPL gene have shown that exons and introns are essential for gene expression and regulation. However, mechanisms through which introns regulate gene expression and function remain unclear. In this study, we successfully designed a protocol to assess the function of LPL intron 3 in LPL regulation. This was accomplished by constructing luciferase reporter vectors, containing full and partial intron 3 fragments from a healthy human DNA sample. These recombinant constructs facilitated the analysis of transcriptional activity using dual-luciferase reporter assays in cell lines. The results showed that the luciferase activity of the chimeric firefly luciferase reporter construct containing the full-length LPL intron 3 was higher than that of other constructs. In this study, a successful protocol was developed to assess the function of LPL intron 3 in regulation of the LPL gene. This protocol provides a novel method for functional analysis of introns and intronic variants that can be applied to other genes.